The effects of ethanol on the size-exclusion characteristics of type i dentin collagen to adhesive resin monomers - Chiba, A.; Zhou, J.; Nakajima, M.; Tan, J.; Tagami, J.; Scheffel, D. L.S. [UNESP]; Hebling, J. [UNESP]; Agee, K. A.; Breschi, L.; Grégoire, G.; Jang, S. S.; Tay, F. R.; et al. (Elsevier, 2016)
During dentin bonding with etch-and-rinse adhesive systems, phosphoric acid etching of mineralized dentin solubilizes the mineral crystallites and replaces them with bound and unbound water. During the infiltration phase of dentin bonding, solvated adhesive resin comonomers are supposed to replace all of the unbound collagen water and polymerize into copolymers. A recently published review suggested that dental monomers are too large to enter and displace water from tightly-packed collagen molecules. Conversely, recent work from the authors' laboratory demonstrated that HEMA and TEGDMA freely equilibrate with water-saturated dentin matrices. However, because adhesive blends are solvated in organic solvents, those solvents may remove enough free water to allow collagen molecules to come close enough to exclude adhesive monomer permeation. The present study analyzed the size-exclusion characteristics of dentin collagen, using a gel permeation-like column chromatography technique, filled with dentin powder instead of Sephadex beads as the stationary phase. The elution volumes of different sized test molecules, including adhesive resin monomers, studied in both water-saturated dentin, and again in ethanol-dehydrated dentin powder, showed that adhesive resin monomers can freely diffuse into both hydrated and dehydrated collagen molecules. Under these in vitro conditions, all free and some of the loosely-bound water seems to have been removed by ethanol. These results validate the concept that adhesive resin monomers can permeate tightly-bound water in ethanol-saturated collagen molecules during infiltration by etch-and-rinse adhesives. Statement of Significance It has been reported that collagen molecules in dentin matrices are packed too close together to allow permeation of adhesive monomers between them. Resin infiltration, in this view, would be limited to extrafibrillar spaces. Our work suggests that monomers equilibrate with collagen water in both water and ethanol-saturated dentin matrices.
Keywords: Bound water; Collagen; Dentin; Ethanol-wet bonding; Mineralized collagen; Polar solvents; Resin-dentin bonding; Size-exclusion